2022
DOI: 10.3389/fnut.2022.842766
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Artemisia Polysaccharide Fermentation Process by Aspergillus niger

Abstract: In order to investigate the fermentation process of Artemisia polysaccharides, this paper showcases an investigation into the effects of fermentation time, fermentation temperature, strain inoculum, Artemisia annua addition, and shaker speed on the polysaccharides production of Artemisia annua. The yield of Artemisia polysaccharides content was determined based on the optimization of single-factor test, and then a response surface test was conducted with temperature, inoculum, and time as response variables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The antioxidant properties of natural polysaccharides were usually estimated by in vitro approaches such as total reducing power (TRP), DPPH, and ABTS free radical scavenging activities (Tao et al, 2022), which equipped with both speed and simplicity. Based on Figure 3, the antioxidant activity of CYPP‐1 displayed a dose‐dependent relationship with the concentration range of 0.75–3.75 mg/ml, with the highest TRP value of 0.169 ± 0.001 and DPPH and ABTS scavenging activities of 73.66 ± 2.39% and 66.31 ± 0.85%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant properties of natural polysaccharides were usually estimated by in vitro approaches such as total reducing power (TRP), DPPH, and ABTS free radical scavenging activities (Tao et al, 2022), which equipped with both speed and simplicity. Based on Figure 3, the antioxidant activity of CYPP‐1 displayed a dose‐dependent relationship with the concentration range of 0.75–3.75 mg/ml, with the highest TRP value of 0.169 ± 0.001 and DPPH and ABTS scavenging activities of 73.66 ± 2.39% and 66.31 ± 0.85%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant properties of natural polysaccharides were usually estimated by in vitro approaches such as total reducing power (TRP), DPPH, and ABTS free radical scavenging activities (Tao et al, 2022), which equipped with both speed and simplicity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…2C, the antifungal activity rst increased with the increase of the amount of inoculation, reaching the peak when the amount of inoculation is 2%, and then shows a downward trend. The reason may be that the production of antimicrobial substances continues to increase over time, but because SL-44 is an aerobic bacterium, the number of bacteria in the culture medium is too much, resulting in the rapid consumption of nutrients, which makes the number of antifungal substances continue to decrease (Tao et al 2022). Therefore, 2% of the inoculation amount was selected for the follow-up test.…”
Section: Optimal Fermentation Conditions Obtained By the Single Facto...mentioning
confidence: 99%
“…Polysaccharide, comprising of more than ten monosaccharides, is one of the four basic substances that make up life, found in animal cell membranes and cell walls of plants and microorganisms ( 1 ). Previous studies have also demonstrated that polysaccharide has the effects of antitumor, antifatigue, postponing aging, reducing blood lipid, hypoglycemic activity, and so on ( 2 , 3 ). Moreover, traditional separation methods of polysaccharides from natural materials have been associated with longer extraction time, lower efficiency, and environmentally disastrous ( 4 ).…”
Section: Introductionmentioning
confidence: 99%